Neuroprotective Effects of VEGF-A Nanofiber Membrane and FAAH Inhibitor URB597 Against Oxygen–Glucose Deprivation-Induced Ischemic Neuronal Injury - Wang, Da-Peng; Jin, Kai-Yan; Zhao, Peng; Lin, Qi; Kang, Kai; Hai, Jian (International journal of nanomedicine, 2021)
Brain ischemia is a common neurological disorder worldwide that activates a cascade of pathophysiological events involving decreases in oxygen and glucose levels. Despite substantial efforts to explore its pathogenesis, the management of ischemic neuronal injury remains an enormous challenge. Accumulating evidence suggests that VEGF modified nanofiber (NF) materials and the fatty-acid amide hydrolase (FAAH) inhibitor URB597 exert an influence on alleviating ischemic brain damage. We aimed to further investigate their effects on primary hippocampal neurons, as well as the underlying mechanisms following oxygen-glucose deprivation (OGD). Different layers of VEGF-A loaded polycaprolactone (PCL) nanofibrous membranes were first synthesized by using layer-by-layer (LBL) self-assembly of electrospinning methods. The physicochemical and biological properties of VEGF-A NF membranes, and their morphology, hydrophilicity, and controlled-release of VEGF-A were then estimated. Furthermore, the effects of VEGF-A NF and URB597 on OGD-induced mitochondrial oxidative stress, inflammatory responses, neuronal apoptosis, and endocannabinoid signaling components were assessed. The VEGF-A NF membrane and URB597 can not only promote hippocampal neuron adhesion and viability following OGD but also exhibited antioxidant/anti-inflammatory and mitochondrial membrane potential protection. The VEGF-A NF membrane and URB597 also inhibited OGD-induced cellular apoptosis through activating CB1R signaling. These results indicate that VEGF-A could be controlled-released by LBL self-assembled NF membranes. The VEGF-A NF membrane and URB597 displayed positive synergistic neuroprotective effects through the inhibition of mitochondrial oxidative stress and activation of CB1R/PI3K/AKT/BDNF signaling, suggesting that a VEGF-A loaded NF membrane and the FAAH inhibitor URB597 could be of therapeutic value in ischemic cerebrovascular diseases.